Potret Peran Pajak Daerah pada Saat Sebelum dan Setelah Pandemi Covid-19 - Nova W. P, Elviana Andrian; Chamalinda, Khy’sh Nusri Leapatra (Jurnal Pendidikan Akuntansi (JPAK), 2023)
Covid-19 pandemic is a challenge for the regional government of Nganjuk Regency which is currently intensively realizing massive regional development. Various special policies continue to be made in order to optimize regional taxes as PAD source. This study aims to explore growth rate, effectiveness, and contribution of local taxes as a PAD source between before and after the Covid-19 pandemic, also the role of the Bapenda in efforts to increase regional taxes as PAD source. This study uses a quantitative descriptive method. The results of the study show that the growth rate of local taxes over a period of three years has a positive value indicating an increase in revenue performance during the Covid-19 pandemic. Judging from the effectiveness analysis, local tax performance is still categorized as very effective despite the reduced target in 2020 as a result of the Covid-19 pandemic. On the other hand, the contribution of local taxes as a PAD source is categorized as moderate and has always decreased in the last three years. Entertainment tax is a local tax that has the lowest growth, effectiveness, and contribution rates over the last three years, so that the role of Bapenda as an authorized agency is needed. This research also shows that there were not many differences in the role of Bapenda between before and after the Covid-19 pandemic. The lack of awareness and compliance of taxpayers is the main obstacle that forces Bapenda to be directly involved in implementing various work programs.